How does spatial micro‐environmental heterogeneity influence seedling recruitment in ironstone outcrops? - Dayrell, Roberta L. C.; Fuzessy, Lisieux Franco; Azevedo, Luísa O.; Lambers, Hans; Veneklaas, Erik J.; Silveira, Fernando A. O.; Kikvidze, Zaal (Journal of vegetation science, 2021)
Questions Environmental filters limit the set of potentially coexisting species in plant communities. Paradoxically, some of the world's most biodiverse communities are subjected to strong abiotic filters. We explored how environmental heterogeneity provides conditions for niche segregation in a harsh megadiverse ecosystem, focusing on fine‐scale factors that drive seedling recruitment. Due to the environmental stress (mainly nutrient and water scarcity), we expected the prevalence of positive plant interactions over negative ones to contribute to species coexistence. Location Ironstone outcrop (canga) at Serra da Calçada, southeast Brazil. Methods We characterised microhabitats with one or neither of two dominant shrubs Mimosa calodendron (Fabaceae) and Lychnophora pinaster (Asteraceae), and assessed which micro‐environmental attributes affect seedling survival, growth, and abundance, as well as adult richness in the ecosystem. Results Spatial heterogeneity in the community was mostly driven by differences in substrate properties, and plots with Mimosa calodendron and Lychnophora pinaster exhibited different biotic and abiotic conditions from those lacking these species. Microhabitats under both shrubs had greater adult richness, and those occupied by Mimosa calodendron had greater seedling abundance, suggesting positive effects of environmental conditions associated with these plants. Nevertheless, we identified two potential negative plant–plant interactions: larger crown area of the two dominant shrubs was associated with lower species richness, and greater understorey plant cover with lower seedling abundance. Over one year, 63% of the recorded seedlings survived, but measured attributes failed to predict survival. Seedling relative growth rates were species‐specific and lower in microsites where the rocky substrate is fragmented. The most abundant seedling taxa occurred in association with specific microhabitats. Conclusions Our study suggested that fine‐scale spatial heterogeneity determines the outcome of plant–plant interactions in a stressful ecosystem. Micro‐environmental heterogeneity allows for the spatial segregation of species recruitment, thereby broadening the range of viable strategies within a harsh megadiverse ecosystem. We investigated fine‐scale drivers of seedling recruitment in a harsh megadiverse ecosystem. Seedling abundance and species richness were greater under the two dominant shrub species, but negatively affected by plant cover, suggesting that micro‐environmental variables determine the outcome of plant–plant interactions. The most abundant seedling taxa occurred in association with specific microhabitats, indicating niche segregation of recruitment within the plant community.